LANDASAN YURIDIS GUGATAN PEMBATALAN PERJANJIAN BUILD OPERATE TRANSFER - Thamrin, Husni (STIH Awang Long Samarinda, 2018)
The non-fulfillment of the BOT agreement in the context of civil law brings with it certain legal consequences. Subject to the provisions of Article 1267 Burgerlijk Wetboek (BW) there are 4 legal consequences of non-fulfillment of obligations under the agreement, including the BOT agreement, namely (1) Pay the losses suffered by the creditor, (2) Cancellation/termination of the agreement, (3) The existence of risk transition, and (4) Pay the court fee in court. The legal consequences of non-fulfillment of obligations in the BOT agreement are those who feel disadvantaged may request to the noncompliance party to perform the obligation, perform the obligation with compensation, solicitation, or cancel the agreement, or cancellation of the agreement with compensation.